Genetics and the elite athlete: Our understanding in 2020 - John, R.; Singh Dhillon, M.; Dhillon, S. (Indian Journal of Orthopaedics, 2020)
Modern competitive sport has evolved so much that athletes would go to great extremes to develop themselves into champions; medicine has also evolved to the point that many genetic elements have been identified to be associated with specific athletic traits, and genetic alterations are also possible. The current review examines the published literature and looks at three important factors: genetic polymorphism influencing sporting ability, gene doping and genetic tendency to injury. The ACTN3 gene has an influence on type II muscle fibres, with the R allele being advantageous to power sports like sprinting and the XX genotype being associated with lower muscle strength and sprinting ability. The ACE gene polymorphisms are associated with cardio-respiratory efficiency and could influence endurance athletes. Many other genes are being looked at, with specific focus on those that are potentially related to enhancement of athletic ability. Recognition of these specific gene polymorphisms brings into play the concept of genetic engineering in athletes, which constitutes gene doping and is outlawed. This has the potential to develop into the next big threat in elite sports; gene doping could have dangerous and even fatal outcomes, as the knowledge of gene therapy is still in its infancy. Genetic predisposition to injury is also being identified; recent publications have increased the awareness of gene polymorphisms predisposing to injuries of ligaments and tendons due to influence on collagen structure and extracellular matrix. Ongoing work is looking at identifying the same genes from different races and different sexes to see if there are quantitative racial or sexual differences. All of the above have led to serious ethical concerns; in the twenty-first century some sports associations and some countries are looking at genetic testing for their players. Unfortunately, the science is still developing, and the experience of its application is limited worldwide. Nevertheless, this field has caught the imagination of both the public and the sportsperson, and hence the concerned doctors should be aware of the potential problems and current issues involved in understanding genetic traits and polymorphisms, genetic testing and genetic engineering.